Rapid isolation method for extracellular vesicles based on Fe3O4@ZrO2 - Ma, Cuidie; Xu, Zhihui; Hao, Kun; Fan, Lingling; Du, Wenqian; Gao, Zhan; Wang, Chong; Zhang, Zheng; Li, Ningxia; Li, Qi; Gao, Qi; Yu, Changyuan (Frontiers in Bioengineering and Biotechnology, 2024)
Extracellular vesicles (EVs) are pivotal in intercellular communication, disease mechanisms. Despite numerous methods for EVs isolation, challenges persist in yield, purity, reproducibility, cost, time, and automation. We introduce a EVs isolation technique using Fe3O4@ZrO2 beads. Leveraging ZrO2phosphate interaction, EVs were efficiently separated from large volumes of samples in 30 minutes without preconcentration. Our method demonstrated capture efficiency (74%-78%) compared to ultracentrifugation, purity (97%), and reproducibility (0.3%-0.5%), with excellent linearity (R 2 > 0.99). EVs from urine samples showed altered expression of miRNAs. The logistic regression model achieved an AUC of 0.961, sensitivity of 0.92, and specificity of 0.94. With potential for automation, this magnetic bead-based method holds promise for clinical applications, offering an efficient and reliable tool for EVs research and clinical studies.